Didactics of university research - Santiago Poma, Enrique Isidro (2022)
Researching based on context is feasible and reliable. Young university students enter their previous knowledge through a teaching of research teachers. University Law 30220 encourages and promotes research, it is the task of the university, family and society to merge purposes from the basic education classrooms. How to awaken interest in research? Through readings; however, it is paradoxical. Today, there are endless factors about scientific understanding. Require reading practice to develop research topics. Likewise, the didactics of research with critical, creative and reflective thinking guidelines consolidate the process of understanding teaching and learning between teacher and student in the field of quantitative and qualitative sciences.